Where Have All the Resultant Theories Gone?: A Case Study of LGBTIQ+ Homelessness Research to Consider the State of Grounded Theory - Brodie Fraser; Elinor Chisholm; Nevil Pierse (International Journal of Qualitative Methods)
One of the key components of a grounded theory study is the creation of a theory grounded in the data collected. However, it is common to read articles that utilise grounded theory but do not present, nor mention the creation of, a resultant grounded theory despite it being a fundamental part of the method. In this State of the Methods paper, we explore this phenomenon, including in our own work, and provide a case study of a grounded theory that was created as part of a PhD on LGBTIQ + homelessness. We provide this as a resource for those new to grounded theory, who may be struggling with how to create and present a grounded theory. We end with a discussion on ways forward to ensure the rigour of grounded theory remains.